MASS MEDIA: ANALYSIS OF COMMUNICATION PATTERNS BETWEEN PARENTS AND CHILDREN - Husin Husin; Hj. Salamah; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Social media creates change in the world. Social media is the most crucial medium used in obtaining information. Various types of social media have been attached to community activities, one of which is Instagram. On the Instagram account @Parentaltalk.id where a video of a child aged about 12 begging his father to give him a break, telling his father that he needs "life balance" and that "even a robot" cannot handle the amount of work his father requires in order to study continuously . The child freely expresses his feelings for his father and the father does not interrupt the child's conversation and can accept the child's complaints well without having to scold a child. Communication within the family is an important factor in determining whether a child is good or bad. If communication in the family is harmonious, then the child will really feel that he is very valuable, so that it will foster good attitudes and behavior in the child. This study aims to analyze communication patterns between a child who is frustrated in learning because he does not have time to play. The method in this research is library research. The type of research used is mass media analysis, namely observing and analyzing a mass media. The data analysis technique uses the semiotics of Charles Sanders Pierce, who put forward the theory of a triangle of meaning which consists of three main elements, namely the sign, the object and the interpretant. The results of the study show that communication patterns between children and their fathers sometimes go well, but there are still some that are not good. thus causing worry and anxiety for every parent. The results of the study also show the attitude of children who can express their feelings and frustrations well with their fathers as well as the attitude of a father who provides a safe and free space for his children to express feelings and voice opinions